Effects of self-talk on football players performance in official competitions - Daftari, O.; Omar Fauzee, Mohd Sofian; Akbari, A. (Islamic Azad University, Central Tehran Branch, 2010)
One of the factors influencing the athletes’ performance in critical situations is their awareness of the strategies entailing mental skills. One such skill is self-talk that has been identified as an effective mental training tool in controlling human beings’ behaviors. This study aims to examine the perceived positive and negative effects of self-talk on the athletes’ performance. Data were collected through survey questionnaire from a group of Iranian elite football players qualified for national football team. The players’ responses were thematically analyzed for both positive and negative effects of ST in different occasions around official football competitions. The analysis indicated the perceived effects could be characterized at two levels: mental and behavioural. Most important positive effects of ST at mental level included its cognitive benefits such as enhancing focus and attention, promote decision making skills and decreasing reaction time. Mental level benefits also comprised emotional effects of ST such as motivating players to increase efforts, coping with difficult situations, and decreasing anxiety and psyching up. Emotional effects had negative aspects too. Weakening confidence by self-criticism, and dwelling on negative thoughts and increased stress were among negative effects. At behavioral level, ST was perceived to benefit execution of tasks by increased attentional focus and creating an awareness of the negative consequences of certain behaviors thereby benefiting the overall performance of the individuals and that of the team. Implications for football players and team managers have been discussed.